Technology-Based Learning Models and Project-Based Learning Models Work Together to Boost Student Motivation and Abilities - Fadhilah, Roni Yudi; Efendi, Agus; Pramono, Sidik (Faculty of Teacher Training and Education Universitas Sebelas Maret Surakarta, 2024)
The modern industrial era demands more practical and innovative skills from school graduates. As a result, there is a need for educational reform that emphasizes helping students acquire competencies relevant to the demands of the labor market. Technology-based learning (TBL) and project-based learning (PjBL) are two learning strategies that could increase student motivation and proficiency. PjBL offers a project-based learning environment where students can gain knowledge through hands-on experiences closely linked to the business world. TBL provides access to tools, resources, and digital platforms that can enrich learning, increase student engagement, and facilitate wider access to information. An observational method was combined with a qualitative approach in this study. The research sample involved were students at the Vocational High School (SMK) level. The research data were obtained through direct observation of the learning process and student activities. The data were analyzed qualitatively descriptively to explore how integrating PjBL and TBL models can improve student motivation and competence. The study's findings demonstrated that by providing students with more engaging, useful, and pertinent learning material, the integration of PjBL and TBL models can boost their motivation to learn. In addition, active involvement in projects and the use of technology increased students' critical thinking skills, creativity, and ability to adapt to a dynamic work environment. The results of this study suggest that combining TBL and PjBL models could be a useful strategy for encouraging students to learn and develop the skills required in today's industrialized society. Combining these two models into instructional strategies promotes deeper student engagement and equips students with skills that will meet industry demands in the future